High density mapping guided partial antral ablation for a pulmonary vein isolation - Jongmin Hwang (Nature Portfolio, 2021)
Abstract The muscular discontinuities at the pulmonary vein (PV)–left atrial (LA) junction are known. The high-density mapping may help to find the muscular discontinuity. This study evaluated the efficacy of a partial antral ablation for a pulmonary vein (PV) isolation using high density (HD) mapping. A total of 60 drug-refractory atrial fibrillation (AF) patients undergoing catheter ablation were enrolled. The detailed activation mapping of each PV and LA junction was performed using an HD mapping system, and each PV segment’s activation pattern was classified into a “directly-activated from the LA” or “passively-activated from an adjacent PV segment” pattern. The antral ablations were performed at the directly-activated PV segments only when the PV had “passively-activated segments”. If the PV did not contain passively-activated segments, a circumferential antral ablation was performed on those PVs. A “successful partial antral ablation” was designated if the electrical isolation of targeted PV was achieved by ablation at the directly-activated segments only. If the isolation was not achieved even though all directly-activated segments were ablated, a “failed partial antral ablation” was designated, and then a circumferential ablation was performed. Among 240 PVs, passively-activated segments were observed in 140 (58.3%) PVs. Both inferior PVs had more passively-activated segments than superior PVs, and the posteroinferior segments had the highest proportion of passive activation. The overall rate of successful partial antral ablation was 85%. The atrial tachyarrhythmia recurrence was observed in 10 patients (16.7%) at 1-year. HD mapping allowed the evaluation of the detailed activation patterns of the PVs, and passively-activated segments may represent muscular discontinuity. Partial antral ablation of directly-activated antral segments only was feasible and effective for a PVI.